The Implementation Of E - Commerce Entrepreneurs Craftsmen Crocodile Skin: (Case Study Daniel Skin) - Selfina Pare (International Journal of Science, Technology & Management, 2021)
The implementation of E-Commerce Entrepreneurs Craftsmen Crocodile Skin ( Case Study Daniel the Skin) is Used as a means of supporting the business processes that occur on Daniel's Skin which is not yet using the internet media. During this time Daniel Skin Merauke only promote their business place with the print media, radio, and business cards. Daniel skin not promote products through the internet so that the scope of marketing its products has not been extensive, in addition, the sales process is still using a manual system the customer where the consumer has to come to Daniel's skin to conduct a transaction. Daniel Skin needs an E-Commerce application that is able to help to promote their products, and make the process a transaction become more varied, as well as help make the reporting sales of more detailed, so that the productivity of Daniel the Skin can be maximized. Metrode used in this study is the Waterfall method. Applications created with Tools or software support such as Dreamweaver,PHP,Database MySQL And CSS Photoshop. The results of the research and testing of the system performed as a supporting media to help Daniel Skin to maximize the sales of their products and help increase the turnover of their income.